Identificação dos mecanismos entomotoxicos de dois compostos inseticidas naturais em modelo experimental alternativo de insetos: extrato contendo anatoxina-a(s) e jaburetox - Santos, Douglas Silva dos (2019)
The risk assessment is a stage that aims at the evaluation and characterization of the toxic properties of xenobiotic compounds, conditions of exposure to humans and the environment. The aim of this work was to contribute to the evaluation of the risk potential of natural xenobiotic compounds as Anatoxin-a (s) and Jaburetox, by investigating the mechanisms of entomotoxicity in alternative insect models. In the cerebral homogenates of cockroaches, both extract containing anatoxin-a(s) CECA and trichlorfon (Tn) inhibited acetylcholinesterase activity (AChE). In addition, CECA caused a change in the locomotor pattern of cockroaches characterized by a decrease in distance travelled, increasing the frequency and duration of immobility episodes in a manner similar to that observed with trichlorfon (Tn) organophosphate. CECA also induced an increase in leg grooming activity, but not in antenna grooming activity, similar to the effect of Tn. The CECA and Tn induced negative chronotropism in the insect's heart. It was also found that CECA, Tn, and neostigmine induced a neuromuscular block in vivo preparations of the cockroaches of the species Nauphoeta cinerea. On the other hand, jaburetox (Jbtx), an insecticidal peptide derived from the Canavalia ensiformis urease, has no elucidated mechanism of action, despite interacting with the nervous system of insects. In this work, behavioral, electromyographic and electrophysiological protocols were used to identify the cellular and molecular targets involved in the entomotoxicity of Jbtx in cockroaches and locusts. Jbtx caused a change in the locomotor behavior of the insects characterized by a significant decrease in the distance travelled, followed by an increase in the immobility time in N. cinerea. Jbtx also increased the grooming activity of legs and antennae. Jbtx induced a neuromuscular block in vivo and cardiotoxicity in N. cinerea characterized by the decrease in heart rate of cockroaches. Records of muscle and peripheral nerve potentials of the locusts of the species Locusta migratoria demonstrated that Jbtx increases the amplitude of nerve action potentials without altering the muscle profile. Analysis of voltage clamp in Xenopus laevis heterologously expressed with voltage-dependent sodium channels of Blatella germanica of type BgNaV 1.1, demonstrated that Jbtx increases the amplitude of the sodium currents. The set of unpublished data obtained in this work should contribute in a decisive way improving the effectiveness of the analysis within the environmental risk assessment for the studied compounds, contributing with the optimization of the environmental detection and decontamination processes. Nevertheless, due to the inherent biotechnological context of this work, the toxins studied here may in the near future be used as prototypes for the development of new drugs or pesticides of natural origin.